Bughat dalam Perspektif Al-Qur’an: Studi Komparasi Tafsir Al-Azhar Karya Buya Hamka dan Tafsir Al-Misbah Karya Quraish Shihab - Walikhsan, Adli; Simamora, Nur Aisah; Akhyar, Sayed (TSAQOFAH, 2024)
Bughat in the Perspective of the Al-Qur'an (Comparative Study of Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Misbah by Quraish Shihab)" is the result of literature research aimed at answering various questions regarding the meaning of bughat in Al-Qur'an. Qur'an, how Buya Hamka and Quraish Shihab interpret bughat in the Qur'an, and what influence bughat has on aspects of people's lives. The data in this research uses qualitative research techniques, namely data is collected and quoted by analyzing the interpretive science approach. This approach uses a comparison method between two Mufassir, namely Buya Hamka and Quraish Shihab. The primary data source in this research is the verses of the Al-Qur'an using QS. Al-Hujurat verse 9 as the main object of study is supplemented with other verses in the Al-Qur'an. From this research we can conclude that, bughat is an act that exceeds the limits and is unjust carried out by individuals or groups or groups. The topic of this research is a very important topic to study because if it is not understood systematically it will be fatal and the seeds of violence against the state and religion will emerge. Furthermore, these two Mufassir gave an interpretation of the meaning of bughat which was not much different because the style of interpretation they used was adabi ijtima'i. Buya Hamka interprets bughat as someone who persecutes. Meanwhile, Quraish Shihab interprets bughat as an individual or group who goes beyond limits, violates the law and tries to seize power. The verses in the Qur'an when discussing bughat are not only about politics and power. However, there are also social, legal, cultural, economic problems and even all aspects. This proves that the scope of bughat is very broad and is closely related to aspects of life in society. So attention needs to be paid to prevent social conflicts like this from occurring in society.